Determining highly productive soft winter wheat varieties by economically valuable signs in the zone of the Southern Forest-Steppe of Ukraine - Kholod, S.; Kirian, V.; Ilichov, O.; Liashenko, V.; Karasenko, V. (Scientific Progress & Innovations, 2023)
The study was made to find highly productive soft winter wheat varieties of various environmental and geographical origin by the indicators of yield capacity and its components, biological properties for agro-climatic conditions of the Southern Forest-Steppe Zone of Ukraine. The research was conducted during 2020–2022 in the laboratory and field conditions of Ustymivka Experimental Station of Plant Growing named after V.Ya. Yiriev of the National Academy of Agrarian Sciences of Ukraine. The samples of soft winter wheat were studied by the following characteristics: spike length, number of ears and kernels in the spike, spike density, thousand-kernel weight, kernel weight per spike and plant, yield capacity. 68 samples of soft winter wheat (Triticum aestivum L.) of different origin were the research material. During the whole study period, the following Ukrainian winter wheat varieties showed the highest productivity and yield capacity: Perlyna Polissia, Cassiopea, Hospodarka, Laval, Zorepad Bilotserkivsky, Kubok, Axioma Odeska, Perspektyva Odeska, Hratsiia Bilotserkivska; KSW Ronin, Ange-lus German soft winter wheat varieties as well as Ilona variety from Slovakia. The highest level of spike kernel percentage was registered in the following varieties: Ilona (SVK) and Matrix (DEU) – 48 pcs, Angelus (AUT) and Motrey 2 (UKR) – 44 pcs, Zorepad Bilotserkivsky and Metelytsia Kharkivska (UKR) – 43 pcs. According to the complex of the high level of definite signs expression (spike length, the amount of kernels in the spike, thousand-kernel weight, kernel weight per spike and plant), the following varieties can be singled out: Angelus (AUT), Ilona (SVK), Axioma Odeska, Bilosnizhka, Zorepad Bilotserkivsky, Kesaria Poliska, Metelytsia Kharkivska, MIП Valensiia, Optyma Odeska, Raihorodka, Laval, Hospodarka (UKR), Adel (RUS), KWS Ronin (DEU). A high yield environmental plasticity under the conditions of the Southern Forest-Steppe of Ukraine was found in Polisianka, Metelytsia Kharkivska, Hospodarka (UKR), and Ilona (SVK) varieties